2022
DOI: 10.3390/biomedicines10020501
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Altered Evoked and Non-Evoked Responses in a Heterologous Mouse Model of Endometriosis-Associated Pain

Abstract: The aim of this study was to develop and refine a heterologous mouse model of endometriosis-associated pain in which non-evoked responses, more relevant to the patient experience, were evaluated. Immunodeficient female mice (N = 24) were each implanted with four endometriotic human lesions (N = 12) or control tissue fat (N = 12) on the abdominal wall using tissue glue. Evoked pain responses were measured biweekly using von Frey filaments. Non-evoked responses were recorded weekly for 8 weeks using a home cage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…In this study, we were not able to detect any endometriosis-associated pain behavior in our animals. These results are comparable to other investigators who indicated that no significant difference could be observed in thermal sensitivity between the endometriosis and sham animals 46, 88 , although others do document the presence of endometriosis-related hyperalgesia in mice 16, 44, 80, 81, 85, 8992 . This discrepancy in results could be related to differences in study set-up, and more specifically in the choice of the control group.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, we were not able to detect any endometriosis-associated pain behavior in our animals. These results are comparable to other investigators who indicated that no significant difference could be observed in thermal sensitivity between the endometriosis and sham animals 46, 88 , although others do document the presence of endometriosis-related hyperalgesia in mice 16, 44, 80, 81, 85, 8992 . This discrepancy in results could be related to differences in study set-up, and more specifically in the choice of the control group.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, we implanted adipose tissue in the control animals and we showed that the mice implanted with menstrual endometrium and the control animals were comparable regarding tissue attachment, maintenance and nerve fiber innervation. Indeed, another study also showed limited differences in behavior between mice inoculated with endometrial tissue and mice implanted with adipose tissue 92 . Nevertheless, Castro et al 85 indicated that endometriosis mice displayed increased sensitivity to evoked pain measurements, while sham animals, with attached adipose tissue implants, did not show such behavior.…”
Section: Endometriosis-related Behaviormentioning
confidence: 99%
“…The heterologous model (xenograft) is obtained by implanting a portion of an endometrial biopsy from a human donor into an immunosuppressed mouse [52,53]. Although the implantation rate is around 30%, this percentage can increase to 100% when implants are sewn or glued using tissue adhesive [52].…”
Section: Heterologous Modelsmentioning
confidence: 99%
“…19), immunodeficient mice implanted with endometriotic lesions showed chronic pain behaviour but no significant difference in nerve density (Ref. 20). This also suggests that the mechanisms of pain associated with endometriosis are involved in an abnormality in the pain pathways with complicated pathogenesis.…”
Section: Neurogenesis and Endometriosismentioning
confidence: 99%